One-Stage Laparoscopic Surgery for Pulmonary Sequestration and Hiatal Hernia in a 2-Year-Old Girl - Miyagi, Hisayuki; Honda, Shohei; Hamada, Hiromi; Minato, Masashi; Ara, Momoko W.; Taketomi, Akinobu (European Journal of Pediatric Surgery Reports, 2018)
We herein report a case of one-stage laparoscopic surgery for extralobar pulmonary sequestration (EPS) and hiatal hernia. Our patient was a 2-year-old girl who was diagnosed as a mediastinal mass lesion. Postnatal computed tomography revealed that the mediastinal mass was an EPS. Two weeks after birth, the patient developed gastroesophageal reflux (GER), and esophagography showed a hiatal hernia. At 2 years of age, she underwent one-stage laparoscopic Nissen's fundoplication for GER with resection of the EPS in the posterior mediastinum. The sequestrated lung was grasped via the esophageal hiatus; three aberrant blood vessels were dissected to allow removal of the sequestration through the umbilical port site. The esophageal hiatus was repaired and Nissen's fundoplication was performed laparoscopically. The patient's postoperative course was uneventful, with no recurrence of GER symptoms for 1 year. We conclude that one-stage laparoscopic surgery is useful for patients with EPS and hiatal hernia.
Keywords: pulmonary sequestration; hiatal hernia; gastroesophageal reflux; laparoscopic; one-stage